Game emotional activity training as educational technology (Pedagogy of Higher and Secondary Education, 2013)
Kuzhilna L. V.  Game emotional activity training as educational technology.This article analyses theoretical bases of methodology of teaching as Zaytseva technology that enables multiple sensory channels, provides a flow of information blocks, emphasizes the importance of strong signals. The development of m. Zaitseva to organize a fast-paced space for children of pre-school and school age to give teachers the opportunity to creatively approach the finished programs, educational content, methods of its application (techniques and tricks); make the work items in the research activity, drastically reduce time to mastering the skills of reading and writing professional.
Keywords: theory of learning on the part of the letter read; fast-paced space; cubes